Dominasi Maskulinitas dalam Militer: Analisis Konstruksi Budaya terhadap Gender dalam Militer melalui Film Perang - Putiviola Elian Nasir (Department of International Relations, Universitas Andalas)
The issue of femininity and masculinity has long been a source of controversy, specifically when tied to positions of power, rights and obligations. Many will argue that masculinity dominates those positions of power, one of them being the military. It is an undeniable fact that the number of women soldiers is far below men soldiers. This is almost a universal trend. Using Joshua S. Goldstein’s third hypothesis of “tough men and tender women”, this research attempts to analyze the cultural construction of gender in the military that is present in four war movies dating back from 1957 to a more current one of 2008. The result of this research shows that although there has been a shift in what is considered as acceptable for masculinity, femininity still cannot escape its stereotype.